Historia w służbie polemiki wyznaniowej — na przykładzie kontaktów Rzymu z chrześcijaństwem wschodnim w pismach Piotra Skargi - Kuran, Magdalena; Kaczor-Scheitler, Katarzyna; Kuran, Michał; Szymczak, Dawid; Agnieszka Gralak (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
At the turn of the 16th and the 17th centuries history did not yet possess the status of scientific naturein the modern sense. It constituted however an essential element of the contemporary religious disputesbetween the Catholics and the Reformation polemicists as well as the representatives of the Eastern factionsof Christianity.The author analyses the issue of history in the Church presented works of the Jesuit priest PiotrSkarga which are devoted to the matters of the unification of the Ruthenian Orthodox Church with theHoly See. The works of the royal preacher constitute an interesting subject of analysis since they serve asan example of presenting two traditions of comprehending history: epistemological, which gives the pastevents the role to create sense and rhetoric — which emphasizes the form of expression and the persuasivequality of presenting the past. The conviction that one should seek for the sense of the entire history at its roots, was accompanied by the belief concerning the key role of the author, who by describing the past,was at the same time responsible for credibility of the events presented.The review of the aspects selected out of the historical issues presented in the polemics with EasternChristianity, indicates that for Skarga the past was not only an excellent source of erudition but most of all it served a significant role in the process of comprehending the religious disputes contemporary to the Jesuit.